Analysis of various types of ectopic pregnancies: a five-year review - S., Maheswari; C., Poornima; N., Lalitha; Panicker, Seetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Ectopic pregnancy (EP) is a common, life threatening emergency during the first trimester and a significant cause for maternal morbidity and mortality. In any woman of reproductive age presenting with abdominal pain and vaginal bleeding, ectopic pregnancy should be considered. The objectives of the present study is to determine the incidence, risk factors, clinical presentation, type of ectopic pregnancy, treatment, morbidity and mortality. Methods: Retrospective analysis of case sheets of patients admitted with ectopic pregnancy at PSGIMSR, Coimbatore during the period July 2011 to June 2016 was done. The details noted were age, parity, risk factors previous abortion, previous EP, previous pelvic surgery, intrauterine contraceptive device, tubectomy, history of pelvic inflammatory disease, treatment for infertility, clinical presentation, ultrasound findings, investigations including beta HCG value and hemoglobin level, treatment offered, need for blood transfusion, operative findings and morbidity. Results: During the five year, there were 12,407 deliveries at our hospitals and 88 cases of ectopic pregnancies were managed. The incidence is 6.6/1000 deliveries. Among them 44% belonged to the age group of 25-30 years and multi gravida were 73.8%. Most common risk factors were previous abortion (23.8%) and previous surgeries including caesarean section, tubectomy, appendicectomy, tubal microsurgery (23.8%). Most common presentation was pain abdomen (85.2%). Out of the 88 cases, 73 patients were managed surgically (82.9%) and 11 cases were managed successfully with methotrexate (12.5%). Three of them underwent conservative management and one had Uterine Artery Embolization. Conclusions: Early diagnosis based on risk factors and timely intervention plays a main role in reducing morbidity and mortality associated with ectopic pregnancy.